Suprapatellar synovial hypertrophy and reliability of the novel ultrasound assessment of suprapatellar recess in patients with recent knee injuries or early osteoarthritis - Kluzek, S; Wedatilake, T; McNally, E; Price, A; Judge, A; Watt, F; Arden, N; Newton, J (Elsevier, 2016)
Early through to late stage knee osteoarthritis (KOA) has been linked with effusion-synovitis in the suprapatellar pouch and chronic inflammation has been particularly associated with pain. Recent studies also suggest that synovial hypertrophy (SH), especially when seen in the suprapatellar pouch or Hoffa's fat pad, is an independent predictor for development of radiographic KOA. Persistent SH has been reported in post-traumatic knees. Ultrasound (US) assessment has great potential value as a non-invasive, practical method of measuring chronic inflammation and monitoring response to treatment, both clinically and in future trials. The US technique is an operator-dependent technique and reliability of a standardised US protocol in measuring SH and suprapatellar effusion (SE) has not been investigated in populations at risk of KOA.